(untitled) (Global Journal of Science Frontier Research, 2021)
Debris flow modeling is process oriented approach in nature and considers avalanches, flows, falls and has become necessary to plan, manage and mitigate. There have numbers of empirical equations to depict kinematics of debris flow and scientific simulations. In the current study, the Rapid Mass Movements Software (RAMMS) has employed for natural flow modeling of displaced geophysical mass for parts of Rangamati area in Bangladesh. The digital elevation model (DEM) with 12.5m spatial resolution and supported by related secondary data, various geo-mechanical factors, cues from Voellmy rheological model are used as an important inputs for the model. The simulated result provide spatial variability of different geophysical parameters like pressure, momentum, velocity and height in the affected run-out zone. These outputs provides crucial information on real time landslide hazard mitigation and support to development of early warning systems.